PENGENDALIAN HAMA KUBIS Crocidolomia pavonana F. MENGGUNAKAN EKSTRAK KULIT BUAH JERUK CONTROL OF THE CABBAGE PEST Crocidolomia pavonana F. BY USING ORANGE SKIN EXTRACT - , Herminanto (Pembangunan Pedesaan, 2006)
A research has been done to know effects of orange skin extract on mortality, development, fecundity, and fertility of the cabbage pest Crocidolomia pavonana. The results performed that purut extract could kill 26.67% larvae in laboratory condition, decrease feeding activity, inhibit feeding up to 44.70%, rd th increase developmental time of the 3 and 4 larval instars until 7.00 and 6.67 days. Tested extracts reduced numbers of pupae and adults emerged up to 73.33-85 and 68.33-78.33%. The purut orange skin extract was the most effective to decrease egg fertility and fecundity of female moths.